Acquiring High‐Performance and Stable Mixed‐Dimensional Perovskite Solar Cells by Using a Transition‐Metal‐Substituted Pb Precursor. Issue 18 (21st August 2018) - Zheng, Haiying; Liu, Guozhen; Xu, Xiaoxiao; Alsaedi, Ahmed; Hayat, Tasawar; Pan, Xu; Dai, Songyuan
Abstract: In recent years, as the most promising photovoltaic technology, lead halide perovskite solar cells (PSCs) have become a research hotspot owing to their super‐high power conversion efficiency (PCE) and simple preparation method. However, the toxicity of lead and instability under high humidity and temperature greatly affects their further development. In this study, we investigated three kinds of non‐toxic transition metal cations (Zn 2+, Mn 2+, and Ni 2+ ) at 3 % to partially substitute lead cations and form mixed‐dimensional (MD) perovskites. Among these transition metals, Zn 2+ is the most suitable to replace Pb 2+ and Zn‐MD perovskite device exhibits the best PCE of 18.35 %. In addition, we further studied the humidity and heat stability of methylammonium lead iodide (MA), Zn‐MD, Mn‐MD, and Ni‐MD perovskite devices. Upon exposure to about 50 % relativity humidity (RH) for 800 h, the MA and three MD devices, respectively, maintain 30 %, 81 %, 80 %, and 74 % of their original PCE. After aging at 60 °C for 100 h, the PCEs of the four PSCs retain 40 %, 84 %, 85 %, and 76 % of their starting values, respectively. The results show that the three MD perovskite devices have high humidity and heat stability and using transition‐metal‐substituted Pb can gain long‐term stability and reduced toxicity of PSCs. Abstract : Replacing lead : By employing transition metals Zn 2+, Mn 2+ and Ni 2+ at 3 % to partially substitute Pb 2+, new mixed‐dimensional (MD) perovskites are obtained. The results demonstrate that the Zn‐MD perovskite device exhibits the best photovoltaic performance with the highest power conversion efficiency of 18.35 %. More importantly, the three MD devices all exhibit markedly improved humidity stability under about 50 % relativity humidity and thermal resistance at 60 °C.